PENGARUH E-WOM DAN E-SERVICE QUALITY TERHADAP KEPUTUSAN PEMBELIAN PADA ONLINE SHOP RUMAH AUFA DI TENGGARONG - Maharani, Dita; Ilham, Ilham; Putri, Eva Noorhya Akhmar Ramashan (I-Con Media, 2023)
E-won and E-service Quality in the opinion of experts and previous researchers can influence purchasing decisions. So E-wom and E-service Quality can be considered as a way to attract consumer buying interest so that it leads to purchasing decisions. The purpose of this study was to determine the effect of E-wom and E-service Quality variables simultaneously and partially on purchasing decisions at the Aufa Rumah online shop in Tenggarong and the most dominant variable effect on purchasing decisions at the Aufa Rumah online shop in Tenggarong. The sample in this study was 45 people. The analytical tool used is multiple regression and testing of research hypotheses using the F test and t test. Simultaneously shows that E-wom and E-service quality has a significant influence on purchasing decisions at the Aufa Rumah online shop in Tenggarong, Partially shows that E-wom and E-service have a positive and significant effect on purchasing decisions at the Aufa Rumah online shop In Tenggarong, the most dominant Vaiabel in this study was E-wom, so the fourth hypothesis proposed that E-wom had a dominant influence was accepted because it proved its truth.